A Systematic Review of Comorbidity Measurement Methods for Patients With Nontraumatic Brain Injury in Inpatient Rehabilitation Settings. (November 2017) - Khuu, Wayne; Chan, Vincy; Colantonio, Angela
Abstract : Abstract: This review summarizes comorbidity measurements used on patients with nontraumatic brain injury in inpatient rehabilitation and describes findings on measurement validation and comorbidity profiles. MEDLINE and MEDLINE In-Process, EMBASE, PsycINFO, the Cochrane Database of Systematic Reviews, Health, and Psychosocial Measurement Instruments were searched. Two reviewers screened results according to predefined inclusion and exclusion criteria. Population, statistical methods, comorbidity measurement, justification of its use, and results involving comorbidity were extracted using a standard table. Of 9476 articles retrieved, 16 were included. Comorbidity has been measured using various methods including the following: number and type within various classification systems, such as the International Disease Classification system, the Charlson comorbidity index, Centers for Medicare and Medicaid Services comorbidity tiers and patient comorbidity and complexity level values and subsets of diagnoses within nonadministrative data studies. No studies have assessed the predictive ability of the comorbidity measurements for inpatient rehabilitation outcomes in this population. Because comorbidities are common among the nontraumatic brain injury population, the predictive validity of comorbidity measurements should be assessed to determine the most appropriate measure to predict or risk adjust rehabilitation outcomes, which has implications for the development of clinical guidelines, and to inform health service research, planning, and delivery. Abstract : Supplemental digital content is available in the text.